Improvement of the cyclohexanе oxidation process - Ludyn, Anatoly; Reutskyy, Viktor (Technology audit and production reserves, 2017)
Cyclohexane oxidation is object of this research. One of the most problematic points of this process is low conversion of raw material and low selectivities for aim-products at conversions higher than 4 %. One of the reasons for this is absence of modern effective catalytic systems that could increase mentioned indexes. One of successful directions in search of effective catalysts for this process is creation of binary catalytic systems with use of active oxygen-containing additives and industrial catalyst – cobalt naphthenate. During this research we used oxygen-CN-containing compound – Bis-2-cianethyl ether. We determined positive impact of researched oxygen-containing additive at main technical-economical indexes of the process of cyclohexane oxidation – selectivity for oxidation products and ratio of aim-products. Selectivity for aim products increases at 3–4 % in comparison with oxidation at industrial catalyst and remains maximal – 73 % at conversion two times higher than industrial – 7.3 %. It is determined that in presence of researched binary catalytic system at conversion higher than 4 % quantity of formed acids increases to 20.3 %. Therefore we propose method of utilization of formed acids by etherification with alcohol. This provides opportunity of wider use of all products of cyclohexane oxidation. In comparison with similar known methods oxidation in presence of binary catalytic system: cobalt naphthenate – Bis-2cianethyl ether allows decrease of production cost.